A Retrospective study of 130 cases in all age group presented with palpable head and neck swelling - Dr. Falguni Patel; Dr. R. N. Gonsai; Dr. M. L. Patel; Dr. Nasrin Qureshi; Dr. Maulik Vora (Tropical Journal of Pathology and Microbiology, 2018)
Introduction:FNAC is a simple, quick, inexpensive and minimally invasive technique for early diagnosis of palpable lesions in Head and neck. It is usually performed in outpatient department with nearly no complications.Objectives:To evaluate the role of FNAC and its utility in the diagnosis of palpable head and neck masses. To study the spectrum of head and neck lesions and its correlation with age, sex, and frequency of occurrence and its categorization into various groups.Methods:A study was conducted over a period of one year and two months by pathology department, SMS hospitals and Dr. M.K.Shah Medical College, Ahmedabad. Total 130 cases of Head and neck lesions were included during the study period. All patients coming from OPD’S of different departmentspresented with head and neck swellingwere included in the study.Result:Out of 130 cases, 59(45%) were male, 71(55%) were female. Head and neck swelling was most common in the age group of 21-30 years (25.3%).Highest number of FNAC was done from lymph node followed by Thyroid gland and Salivary gland respectively. Lymph node swelling were the most common 81(62%), followed by thyroid 28(22%), skin/subcutaneous 12(9%), salivary gland 09(07%).Conclusion:The accuracy of cytology diagnosis is very high if the requisition forms are accompanied with all relevant clinical history along with proper laboratory information. FNAC could differentiate the infective process from neoplastic one and avoids unnecessary surgeries. Thus, FNAC can be recommended as a first line of investigation in the diagnosis of head and neck swellings.